Aplicación de la fractografía al análisis de falla - Sarrate, M.; Marrapodi, M. R.; Ipohorski, Miguel (Comisión Nacional de Energía Atómica; Argentina, 1974)
Fil: Sarrate, M. Comisión Nacional de Energía Atómica; Argentina